Enhancing English Grammar and Writing Competence through a Big Book Project - Wan Jumani, Fauzi; Noor Raha, Mohd Radzuan; Fatimah, Ali; Noor Azlinda, Zainal Abidin (English Language Education Publishing, 2016)
English grammar is not easy to learn especially for non-native speakers. When English grammar is not sufficiently mastered, many non-native speakers become too shy to speak the language. This is particularly true for most of the thirty childcare providers who recently completed three levels of a Communication English course. This short course is part of a two year Knowledge Transfer Programme (KTP) research project from the Centre for Modern Languages and Human Sciences (CMHLS) of Universiti Malaysia Pahang. These educators are members of Association of Pahang State Childcare Providers (PPNP) and their ages range from 21 to 53. Despite English being a second language in Malaysia, for many of these participants, English is more of a foreign language. This paper aims to describe a more unconventional approach of teaching English grammar and Writing skills through a big book project. This approach introduced English grammar in stages through poetry writing and focused on Haikus. At the end, participants produced a big book as a group in class and another big book individually as an assignment. To ensure that their illustrations were cohesive, they were given an art technique to choose from. Feedback received shows that the educators enjoyed learning grammar and writing this way and are inspired to write big books for their respective daycares. Keywords: teaching English Grammar, Big Book Project, Haiku